Service quality attributes: perspective of newly registered postgraduate students by research / Siti Halijjah Shariff, Syazwani Amanina Azman, Nur Fhatihah Zakria - Shariff, Siti Halijjah; Azman, Syazwani Amanina; Zakria, Nur Fhatihah (Faculty of Business and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2016)
For service industry, it is rather difficult to measure quality of service since services are intangible in nature. Nevertheless, effort on measuring service quality will have to be done to form a basis of monitoring, control and planning. This study looks into the service quality attributes of postgraduate programme by research by having newly registered students to participate by answering the survey form. The findings confirm other research in this area in that lecturers play a major role in education. However, leisure seems to be the lower end of agreement if compared to academic, cost and industry link.